Metrology in Urban Drainage and Stormwater Management Plug and Pray - Bertrand-Krajewski, Jean-Luc; Clemens-Meyer, Francois; Lepot, Mathieu (IWA Publishing, 2021)
This book presents the advancements made in applied metrology in the field of Urban Drainage and Storm water Management over the past two decades in scientific research as well as in practical applications. Given the broadness of this subject (measuring principles, uncertainty in data, data validation, data storage and communication, design, maintenance and management of monitoring networks, technical details of sensor technology), the focus is on water quantity and a sound metrological basis. The book offers common ground for academics and practitioners when setting up monitoring projects in urban drainage and storm water management. This will enable an easier exchange of results so as to allow for a faster scientific progress in the field. A second, but equally important goal, is to allow practitioners access to scientific developments and gained experience when it comes to monitoring urban drainage and storm water systems. In-depth descriptions of international case studies covering all aspects discussed in the book are presented, along with self-training exercises and codes available for readers on a companion website.